LEGAL ASPECTS OF SPACE TRAFFIC - Mijović, Milan (Pravni zapisi, 2013)
The second half of the XX century was marked by a fast development of technology and science. Following the codification of aviation law, an idea was born concerning a new branch of international law. As a logical consequence of the development of humanity, space law was born. In 1959, at the proposal of the USA and the USSR, the UN has formed a Committee on the Peaceful Uses of Outer Space. The Committee has a Legal Subcommittee and a Scientific and Technical Subcommittee. As of 1967, five international agreements were adopted, the most important of which is the Agreement Governing the Activities of States on the Moon and Other Celestial Bodies. In addition to these agreements, five declarations on the legal principles concerning space were also adopted. The first UN conference on the exploration and peaceful use of space was held in Vienna in 1968. It was followed by the Second UN Conference, which became known as UNISPACE in 1982. In July 1999, the Third UN Conference was held. It is precisely these five UN agreements and five UN declarations that constitute the main source of space law. However, in addition to the UN, today there is a number of organisations whose role in the formulation of space law is growing – these are the World Trade Organisation and the International Telecommunication Union. In the narrow sense, the legal source of space law can be found in the Space Treaty of 1967. The principles proclaimed in this treaty were later elaborated in the 1972 and 1975 Conventions. On the international level, space law today is still far from being complete. It should be borne in mind that the present provisions constitute a very broad framework, and that more detailed and more elaborate provisions are yet to come. On the other hand, national space law is the right of every state to regulate this field. Hence, the states which have the power to launch differentiate three phases of the process in their legislation: the launch, the orbital and the re-entry phase. In addition, the legislation of some states, such as Russia and Ukraine, envisage various types of information concerning space operation. It is very important to identify the parallel between space law today and aviation law in the beginning of the XX century. Codification of aviation law is complete, and whether the same will happen with space law still remains to be seen. Key words: space law, space, traffic, orbit, satellite, operation, aircraft, safety, Earth.